Effect of whey protein concentrate and endogenous lactic acid bactéria in low-fat Coalho cheese (Research, Society and Development, 2020)
The fat content and lactic ferment are two components that positively influence cheese sensorial properties. However, the consumption of low fat content foods is trending among the consumers. Researches about fat replacers applications have been used as an alternative to elaborate low-fat cheeses associated with good sensorial acceptance. In the same way, the use of specific lactic ferments elaborated from lactic acid bacteria isolated from the cheeses themselves is an alternative to obtain safe products, without promoting fundamental changes in its sensorial characteristics. With aim to evaluate the texture profile (Firmness, Elasticity, Cohesiveness and Chewability) and physicochemical characteristics of low-fat Coalho cheese, the effect of whey protein concentrate - WPC (1, 2 and 3%) and endogenous lactic bacteria - ELB (1, 2 and 3%) was tested. The treatments on the Coalho cheese produced cheeses classified as low-fat (2.33% to 4.67%) and high in protein value (41.01% to 46.95%). The WPC concentrations showed significant effect (p < 0.05) in firmness, cohesiveness and chewability parameters. In conclusion, the use of the WPC as a fat replacer is viable in the Coalho cheese production. However, the addition of ELB as ferment does not influence the Coalho cheese properties.